An observational cross-sectional study to determine the effect of telmisartan on reducing microalbuminuria in diabetic hypertensive patients in tertiary care teaching hospital, Central India - Chenchula, Santenna; Gupta, Rupesh; S., Balakrishnan; Vishwe, Akash; Gour, Pushparaj; Kumar, Sunil (International Journal of Basic & Clinical Pharmacology, 2017)
Background: There are many groups of drugs to decrease microalbuminuria like angiotensin converting enzyme inhibitors (ACEI), angiotensin receptor blockers (ARBs), calcium channel blockers and direct vasodilators. Among these, ACEI and ARBs are commonly used for this purpose. If side effects occur, ACEI are replaced with ARBs. Many ARBs have been studied for their effect on reducing microalbuminuria, but data on telmisartan with its additional unique properties are scarce in Indian population. Methods: This cross sectional observational study was carried out in a tertiary care centre. We first measured base line urine albumin levels in included patients, 3 months after treatment with telmisartan using ‘hemocue urine albumin analyser’. We collected and compared both baseline and after treatment data of microalbuminuria and analysed in descriptive statistics. Results: A total of 110 patients participated in this study; out of which 10 patients were excluded from the study because they were not available for follow up. As compared to baseline, urine albumin level decreased by 30.42% after 12 weeks treatment with telmisartan (P <0.001). Conclusions: Microalbuminuria is one of the leading cause of end stage renal disease and coronary heart diseases in diabetic hypertensive patients. Drugs like ACE inhibitors, Angiotensin receptor blockers, Calcium channel blockers and direct vasodilators are used to prevent these complications. In this present study, we concluded that telmisartan decreases urine albumin excretion around 30.42% from baseline after 12 weeks of treatment.